Strategi Pemasaran Pendidikan dalam Menarik Minat Belajar Calon Peserta Didik Baru di Madrasah Ibtidaiyyah Al-Mursyidiyyah Pamulang Kota Tangerang Selatan - Ihza Rizky Hamdallah; Mohammad Muhtadi; Singgih Aji Purnomo (Al-Tarbiyah : Jurnal Ilmu Pendidikan Islam, 2026)
The increasingly competitive competition between educational institutions requires each school to implement effective marketing strategies to attract prospective new students. This study aims to analyze educational marketing strategies in attracting prospective new students at MI Al-Mursyidiyyah Pamulang, South Tangerang City. The study uses a qualitative approach with a case study research type. Research informants were selected using a purposive sampling technique consisting of the principal, the chairman of the New Student Admissions Committee (PPDB), teachers, and parents of students. Data collection was carried out through observation, interviews, and documentation, while data analysis used the Miles, Huberman, and Saldaña model which includes data condensation, data presentation, and drawing conclusions. The results of the study indicate that educational marketing strategies at MI Al-Mursyidiyyah are implemented through three stages, namely planning, implementation, and evaluation. The planning stage is carried out through coordination between the foundation, the principal, the PPDB committee, and teachers in preparing the marketing program. The implementation phase applies the marketing mix concept, encompassing product, price, place, promotion, people, process, and physical evidence, utilizing both direct and digital promotions, supported by the madrasah's flagship program. The evaluation phase is conducted periodically to assess the effectiveness of the marketing strategy, identify obstacles, and develop program improvements for the next period. The results of the study indicate that the implemented educational marketing strategy has been able to increase public trust and support the interest of prospective new students at MI Al-Mursyidiyyah Pamulang, South Tangerang City.